2000
DOI: 10.1242/dev.127.19.4115
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila disembodied gene controls late embryonic morphogenesis and codes for a cytochrome P450 enzyme that regulates embryonic ecdysone levels

Abstract: Ecdysteroids regulate a wide variety of cellular processes during arthropod development, yet little is known about the genes involved in the biosynthesis of these hormones. Previous studies have suggested that production of 20-hydroxyecdysone in Drosophila and other arthropods involves a series of cytochrome P450 catalyzed hydroxylations of cholesterol. In this report, we show that the disembodied (dib) locus of Drosophila codes for a P450-like sequence. In addition, we find that dib mutant embryos have very l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(27 citation statements)
references
References 59 publications
1
26
0
Order By: Relevance
“…During larval and pupal stages of insects, one of the most important steroid hormones is ecdysone, which is synthesized in the PG and plays a central role in the control of larval development. In this study, two players Cyp302a1 57,58 and Rieske-domain protein Neverland, 59 which are involved in the biosynthesis of ecdysteroids, were identified among the PG-specific proteins (Supplemental Table 6). POU domain proteins which play an important role in transcriptional regulation of the Bom-DH-PBAN gene 60 were also found.…”
Section: Resultsmentioning
confidence: 98%
“…During larval and pupal stages of insects, one of the most important steroid hormones is ecdysone, which is synthesized in the PG and plays a central role in the control of larval development. In this study, two players Cyp302a1 57,58 and Rieske-domain protein Neverland, 59 which are involved in the biosynthesis of ecdysteroids, were identified among the PG-specific proteins (Supplemental Table 6). POU domain proteins which play an important role in transcriptional regulation of the Bom-DH-PBAN gene 60 were also found.…”
Section: Resultsmentioning
confidence: 98%
“…One possibility is that there is an actual clock -some molecule or set of molecules whose abundance or activity progresses in a clocklike manner across embryogenesis and is read out to trigger the myriad different processes that occur in the transition from a fertilized egg to a larvae. However there is no direct evidence that such a clock exists (although we note that there is a pulse of ecdysone during embryogenesis with possible morphological functions [28,29]). A more likely explanation is that there is a common rate limiting process throughout embryogenesis.…”
Section: Uniform Scaling and The Timing Of Embryogenesismentioning
confidence: 99%
“…In D. melanogaster , ecdysteroids control larval development [ 29 , 30 ]. Whereas, in adults, these hormones are found to be essential for proper oogenesis [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila , the application of cyromazine increased larval mortality, while the exogenous treatment of 20E decreased larval mortality. Further, 20E treatment together with cyromazine increased the early eclosion of adult flies [ 30 ]. In the present study, we observed a 27% decrease in the number of GSCs after treatment with cyromazine.…”
Section: Discussionmentioning
confidence: 99%